Identification of Staphylococcus Aureus in Patients Diabetic Ulcus In Bunda Thamrin Hospital Medan - Sinaga, Eka Margaret; Mahyudi (Jurnal Analis Laboratorium Medik, 2022)
Staphylococcus aureus can cause infection that usually presents with characteristic signs of inflammation, necrosis, and abscess formation. Staphylococcus aureus is responsible for 80% of suppurative diseases with the skin surface as its natural habitat. Skin infections and open wounds such as ulcers, burns, and surgical wounds increase the likelihood of bacterial infection and result in systemic infection. Identification of Staphylococcus aureus in diabetic ulcer patients was carried out at the Microbiology Laboratory of Bunda Thamrin Hospital Medan from February to March 2022 with a total sample of 6 people, this study is descriptive Experiment using isolation and identification methods. The results showed that of the 6 samples, 50% of the samples were contaminated with Staphylococcus aureus bacteria, 50% of the samples were contaminated with gram-negative rods. From the results of the study it can be concluded that Staphylococcus aureus is one of the bacteria that causes infection in diabetic ulcer patients. The results showed that of the 6 samples, 50% of the samples were contaminated with Staphylococcus aureus bacteria, 50% of the samples were contaminated with gram-negative rods. The results showed that of the 6 samples, 50% of the samples were contaminated with Staphylococcus aureus bacteria, 50% of the samples were contaminated with gram-negative rods. From the results of the study it can be concluded that Staphylococcus aureus is one of the bacteria that causes infection in diabetic ulcer patients.